Action Research as A Strategic Method to Treat Stunting - Heru Santoso Wahito Nugroho; I Putu Suiraoka; Bahtiar Bahtiar; Pius Selasa; Sanglar Polnok; Handoyo Handoyo; Fransiskus Salesius Onggang; Bringiwatty Batbual; M. Miftachul Ulum; Imam Sunarno; Lina Lina; Zulkarnaini Zulkarnaini; Eva Sulistiany; Elfida Elfida (Alliance oh Health Activists (AloHA), 2021)
Stunting in toddlers is a problem for the world. The causes of stunting are very broad, in the sense that it involves very many factors. Stunting in children under five is one of the main health problems with several characteristics, namely: 1) occurring in a wide scope; 2) involves very diverse determinants; 3) is chronic. Thus, based on logic, the approach used to prevent stunting in children under five must also be relevant to these characteristics. In relation to the first and second characteristics, currently stunting prevention efforts in all regions and levels have been carried out intensively, as well as efforts carried out across programs and across sectors. Evidence-based stunting prevention efforts have also been implemented involving educational institutions and research and development institutions. Evidence based practice in stunting prevention has become a must, so that the efforts made have the right direction, so that they can achieve the expected goals. Keywords: stunting; action research; approach